2016
DOI: 10.1007/s10528-016-9716-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Inferring Phylogenetic Relationships of Indian Citron (Citrus medica L.) based on rbcL and matK Sequences of Chloroplast DNA

Abstract: Phylogenetic relationships of Indian Citron (Citrus medica L.) with other important Citrus species have been inferred through sequence analyses of rbcL and matK gene region of chloroplast DNA. The study was based on 23 accessions of Citrus genotypes representing 15 taxa of Indian Citrus, collected from wild, semi-wild, and domesticated stocks. The phylogeny was inferred using the maximum parsimony (MP) and neighbor-joining (NJ) methods. Both MP and NJ trees separated all the 23 accessions of Citrus into five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, in addition to IGS and introns, we identified a number of coding regions that may prove useful for Salvia phylogenetics. The four protein coding genes with highest π values identified by our study (accD, matK, ndhF, and ycf1) have all been used for phylogenetic inference (Zhang and Li 2004;Chang-Li et al 2012;Cruz et al 2013;Qian et al 2013;Luo et al 2014;Patil et al 2015;Srikulnath et al 2015;Uchoi et al 2016;Devi and Chrungoo 2017;Bengtson and Anderberg 2018;Deng et al 2018;Lei et al 2018;Satoh et al 2018;Veranso-Libalah et al 2018), but only matK and ycf1 Sytsma 2011, 2012;Hu et al 2018) have been utilized in sages.…”
Section: Discussionmentioning
confidence: 97%
“…However, in addition to IGS and introns, we identified a number of coding regions that may prove useful for Salvia phylogenetics. The four protein coding genes with highest π values identified by our study (accD, matK, ndhF, and ycf1) have all been used for phylogenetic inference (Zhang and Li 2004;Chang-Li et al 2012;Cruz et al 2013;Qian et al 2013;Luo et al 2014;Patil et al 2015;Srikulnath et al 2015;Uchoi et al 2016;Devi and Chrungoo 2017;Bengtson and Anderberg 2018;Deng et al 2018;Lei et al 2018;Satoh et al 2018;Veranso-Libalah et al 2018), but only matK and ycf1 Sytsma 2011, 2012;Hu et al 2018) have been utilized in sages.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, both the IGRs and CDSs can serve as useful molecular markers. Some genes (matK, rps16, rbcL, rpl16, ndhA, ndhF, and ycf1) and IGRs (rps16-trnQ, petN-psbM, rps15-ycf1, trnL-trnF) exhibited high nucleotide diversity (Table S2), which have also been used for phylogenetic and phylogeography analyses (Ravi et al, 2007;Chavez et al, 2016;Uchoi et al, 2016;Yang et al, 2016;Khan et al, 2018).…”
Section: Cerasus Cp Genome Features and Genomic Variationmentioning
confidence: 99%
“…These results indicated that multi-region sampling can improve the resolution of the analysis. In addition, two protein-coding genes (rpoB and rbcL), which were considered as having a high level of variability in angiosperms, have been recommended and used for phylogenetic studies (Chase et al 2007;Okoth et al 2016;Uchoi et al 2016;Sha et al 2017;Oyebanji et al 2020). They were also used for understanding the phylogenetic relationships and diversity in subgenus Cerasus (Jung and Oh.…”
Section: Discussionmentioning
confidence: 99%